2014
DOI: 10.1073/pnas.1321716111
|View full text |Cite
|
Sign up to set email alerts
|

Functional evolution of Erg potassium channel gating reveals an ancient origin for I Kr

Abstract: Mammalian Ether-a-go-go related gene (Erg) family voltage-gated K + channels possess an unusual gating phenotype that specializes them for a role in delayed repolarization. Mammalian Erg currents rectify during depolarization due to rapid, voltage-dependent inactivation, but rebound during repolarization due to a combination of rapid recovery from inactivation and slow deactivation. This is exemplified by the mammalian Erg1 channel, which is responsible for I Kr , a current that repolarizes cardiac action pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 46 publications
(55 reference statements)
5
59
0
Order By: Relevance
“…Phylogeny reveals that NvErg1 and the mammalian channels represent the ancestral electrical behavior, whereas NvErg4 evolved in a convergent manner to the Drosophila channel. Surprisingly, it seems that nematode Erg channels also acquired this feature independently, suggesting that this electrical behavior evolved at least three times during animal evolution (Martinson et al, 2014).…”
Section: The Evolution Of Animals and The Genomic Revolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogeny reveals that NvErg1 and the mammalian channels represent the ancestral electrical behavior, whereas NvErg4 evolved in a convergent manner to the Drosophila channel. Surprisingly, it seems that nematode Erg channels also acquired this feature independently, suggesting that this electrical behavior evolved at least three times during animal evolution (Martinson et al, 2014).…”
Section: The Evolution Of Animals and The Genomic Revolutionmentioning
confidence: 99%
“…Moreover, the Shaker gene in the genome of a deuterostome -the sea urchin Strongylocentrotus purpuratus -is intron-less as well (Sodergren et al, 2006), suggesting that chordate and most cnidarian Shaker genes may have evolved from a common intron-less ancestor (Jegla et al, 2012). A recent study of the functional properties of another family of cnidarian K V channels uncovered the properties of ancestral channels: in the study, Martinson et al (Martinson et al, 2014) functionally expressed the Nematostella homologs of the bilaterian Ether-a-go-go related channel (Erg, also known as K V 11.1). One of the Nematostella homologs (NvErg1) exhibits similar electrical characteristics to those of the human channels, whereas another (NvErg4) behaves similarly to the Drosophila channel.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The EAG gene family is comprised of three separate subfamilies classified by high intra-family sequence conservation: Eag, Erg and Elk Jegla et al, 2009). Each subfamily is present in vertebrates and protostome invertebrates, and members of each family have been identified in the genome of the starlet sea anemone Nematostella vectensis Martinson et al, 2014;Putnam et al, 2007), pointing to an origin prior to the cnidarian-bilaterian divergence.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that the Eag, Elk and Erg subfamilies are functionally independent includes the finding that although voltage-gated K + channels are tetrameric, co-assembly of subunits from distinct subfamilies does not occur (Wimmers et al, 2001;Zou et al, 2003). We have previously expressed Nematostella (sea anemone) Erg channel paralogs and demonstrated that an inactivating I Kr -like phenotype of Ether-à-go-go family voltage-gated K + channels evolved in an ancestral metazoan and functionally diversified in a cnidarianbilaterian ancestor mammalian Erg channels is the likely functional phenotype of Erg channels in the cnidarian-bilaterian ancestor (Martinson et al, 2014). Erg channels are specialized for delayed repolarization of broad action potentials and/or regulation of excitation threshold (Garcia and Sternberg, 2003;LeBoeuf and Garcia, 2012;Martinson et al, 2014;Sanguinetti and Tristani-Firouzi, 2006;Titus et al, 1997).…”
Section: Introductionmentioning
confidence: 99%